Determinan Minat dan Keputusan Pembelian Fashion Merek Uniqlo - Aldiansyah, Rangga; Mutmainah, Isbandriyati; Putra, Mulyana Gustira (Jurnal EMT KITA, 2026)
This study aims to examine the influence of Country of Origin, perceived quality, perceived price, and lifestyle on purchasing decisions, with purchase intention as a mediating variable. The study population included all consumers of Uniqlo brand fashion products, with 130 respondents obtained through non-probability sampling using the accidental sampling method. Data analysis was conducted using multiple linear regression with a causal step model. The results showed that Country of Origin, perceived quality, and perceived price had a direct and significant influence on purchasing decisions, while lifestyle had no significant influence. Purchase intention mediated the influence of Country of Origin and perceived quality on purchasing decisions, but did not mediate the influence of perceived price and lifestyle on purchasing decisions. These findings emphasize the importance of country of origin image and product quality in shaping purchasing intentions and driving consumer purchasing decisions.